2009
DOI: 10.1159/000228905
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Nocturnal Hypoxemia with Arterial Stiffness and Endothelial Dysfunction in Male Patients with Obstructive Sleep Apnea Syndrome

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) is associated with cardiovascular complications, and atherosclerosis is considered to mediate this association. Arterial stiffness and endothelial dysfunction are widely accepted as early markers of atherosclerosis. Objectives: The purpose of this study was to investigate the influence of sleep apnea on arterial stiffness and endothelial dysfunction. Methods: We enrolled 83 OSAS patients including 39 with mild to moderate degree (apnea hypopnea index, AHI ≧5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 80 publications
(53 reference statements)
5
52
1
5
Order By: Relevance
“…46 It was found that, whereas both types of OSA patients showed significantly higher arterial stiffness as compared to healthy controls, OSA patients with masked hypertension had the highest arterial stiffness. Chung et al 47 compared cfPWV in patients with mild to moderate OSA, severe OSA and control subjects. They found cfPWV to be significantly higher in patients with severe OSA as compared to both mild to moderate OSA and normal controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 It was found that, whereas both types of OSA patients showed significantly higher arterial stiffness as compared to healthy controls, OSA patients with masked hypertension had the highest arterial stiffness. Chung et al 47 compared cfPWV in patients with mild to moderate OSA, severe OSA and control subjects. They found cfPWV to be significantly higher in patients with severe OSA as compared to both mild to moderate OSA and normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the seven studies investigating the association between severity of OSA and arterial stiffness, 45,47,48,51,52,60,62 six provided full support for the association 45,47,51,52,60,62 and one provided mixed results. 48 More specifically, the study by Protogerou et al 48 did not find a direct association between OSA severity categories (moderate, severe and very severe) and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another recent study, 5 OSA syndrome was shown to increase Rho-associated protein kinase activity and to be a major determinant of endothelial dysfunction. Chung et al 6 also showed that nocturnal hypoxemia may alter arterial elasticity and endothelial function in patients with OSA syndrome.…”
Section: To the Editormentioning
confidence: 97%
“…Several studies have revealed higher PWV in obstructive sleep apnoea (OSA) patients than in controls and reported nocturnal oxygen desaturation to be associated with high PWV 19, 20…”
Section: Introductionmentioning
confidence: 99%